3D‐Stacked Vertical Channel Nonvolatile Polymer Memory. (15th January 2015) - Hwang, Sun Kak; Cho, Suk Man; Kim, Kang Lib; Park, Cheolmin
Abstract : A 3D‐stacked one transistor memory with vertically defined submicrometer channels is realized by carefully designing device architecture involving repetitive deposition of layers in combination with a one‐step bilayer transfer of a ferroelectric layer and a semiconducting one. The devices represent a milestone in the realization of mechanically flexible, one‐transistor polymer memory with high memory performance.